2002
DOI: 10.1023/a:1024887211146
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of hepatitis C virus antibodies among the voluntary blood donors of New Delhi, India

Abstract: Infection with hepatitis C virus (HCV) is a major cause of transfusion-associated hepatitis, cirrhosis and hepatocellular carcinoma. The present study was conducted with an objective to evaluate the prevalence of anti-HCV antibody in New Delhi, India using a large number of healthy voluntary blood donors. A total of 15,898 healthy voluntary blood donors were subjected to anti-HCV testing (using a commercially available third generation anti-HCV ELISA kit) and 249 were found to be reactive for anti-HCV antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 3 publications
7
21
2
Order By: Relevance
“…8 probably we collect majority of the blood through blood donation camps. The prevalence of HIV in present study was 0.11% (12), which is lower than the study done by Bharat S et al 0.8% and another study by Pallavi P et al showed 0.44% (Table 3). 10,11 it has been found that prevalence of HBV, HCV and HIV among blood donors or the general population varied from country to country and place to place.…”
Section: Discussioncontrasting
confidence: 71%
“…8 probably we collect majority of the blood through blood donation camps. The prevalence of HIV in present study was 0.11% (12), which is lower than the study done by Bharat S et al 0.8% and another study by Pallavi P et al showed 0.44% (Table 3). 10,11 it has been found that prevalence of HBV, HCV and HIV among blood donors or the general population varied from country to country and place to place.…”
Section: Discussioncontrasting
confidence: 71%
“…Various studies from northern parts of India have reported HCV seroprevalence ranging from 0.53 to 5.1% in blood donors. 7,21,22 HCV seropositivity in the western part of India has been reported to be 0.28%. 23 The reported variation in the prevalence of anti-HCV antibodies among blood donors in different regions of India may be attributed to the differences in the literacy rate and level of awareness among the blood donors.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Blood transfusion is an important life saving measure and an integral part of Amongst the viral hepatitis strains, Hepatitis C virus (HCV) is most dangerous etiological agent of transfusion-associated hepatitis as its morbidity rate is quite high with around 85% of the acutely infected patients progressing to chronic infection such as liver cirrhosis and hepatocellular carcinoma. 7,8 Blood transfusion is an effective mode of transmission of HCV infection as it allows a large quantum of infective virions into the susceptible patient. 3 It has been shown to be responsible for up to 90 percent of cases, previously known as Non A Non B (NANB) transfusion-related hepatitis.…”
Section: Introductionmentioning
confidence: 99%
“…12,14,15 In a recent study done in Hisar, Haryana, the seroprevalence of anti-HCV antibodies was calculated to be 1 per cent. 16 A study done in Orissa reported anti-HCV seroprevalence to be 1.98 per cent.…”
Section: 13mentioning
confidence: 99%